N-Butyl-4-chlorobenzamide - Saeed, Aamer (International Union of Crystallography, 2008)
In the title benzamide derivative, C(11)H(14)ClNO, the chlorobenzene and butylamine groups are each planar, with mean deviations from the planes of 0.013 and 0.030 Å, respectively, and a dihedral angle of 2.54 (9)° between the two planes. In the crystal structure, N—H⋯O hydrogen bonds link molecules in rows along a. Short intermolecular Cl⋯Cl interactions [3.4225 (5) Å] link these rows into sheets in the ac plane. Additional weak C—H⋯O and C—H⋯π interactions generate a three-dimensional network.